Host Restriction Factors APOBEC3G/3F and Other Interferon-Related Gene Expressions Affect Early HIV-1 Infection in Northern Pig-Tailed Macaque (Macaca leonina) - Pang, Wei; Song, Jia-Hao; Lu, Ying; Zhang, Xiao-Liang; Zheng, Hong-Yi; Jiang, Jin; Zheng, Yong-Tang (Frontiers in Immunology, 2018)
The northern pig-tailed macaques (NPMs) lack TRIM5α, an antiviral restriction factor, and instead have TRIM5-CypA. In our previous study, we demonstrated that HIV-1NL4−3 successfully infected NPMs and formed a long-term viral reservoir in vivo. However, the HIV-1-infected NPMs showed relatively high viremia in the first 6 weeks of infection, which declined thereafter suggesting that HIV-1 NL4−3 infection in these animals was only partly permissive. To optimize HIV-1 infection in NPMs therefore, we generated HIV-1NL4−R3A and stHIV-1sv, and infected NPMs with these viruses. HIV-1NL4−R3A and stHIV-1sv can replicate persistently in NPMs during 41 weeks of acute infection stage. Compared to the HIV-1NL4−R3A, stHIV-1sv showed a notably higher level of replication, and the NPMs infected with the latter induced a more robust neutralizing antibody but a weaker cellular immune response. In addition, IFN-I signaling was significantly up-regulated with the viral replication, and was higher in the stHIV-1sv infected macaques. Consequently, the sequences of pro-viral env showed fewer G-A hyper-mutations in stHIV-1sv, suggesting that vif gene of SIV could antagonize the antiviral effects of APOBEC3 proteins in NPMs. Taken together, NPMs infected with HIV-1NL4−R3A and stHIV-1sv show distinct virological and immunological features. Furthermore, interferon-related gene expression might play a role in controlling primary HIV-1NL4−R3A and stHIV-1sv replication in NPMs. This result suggests NPM is a potential HIV/AIDS animal model.